Sigma Matrix of Ureum and Creatinine in Some Laboratories: Overview: Gambaran Matrik Sigma Pemeriksaan Ureum dan Kreatinin pada Beberapa Laboratorium - Salsabella, Ainun; Aryani, Titin (Medicra (Journal of Medical Laboratory Science/Technology), 2022)
In clinical diagnosis, 80% is based on laboratory examination, however, laboratory examination still often cause errors, so it is necessary to apply a sigma matrix to evaluation. This study goes on to explain the results of previous studies on the sigma urea and creatinine matrix results in various laboratories. A literature review strategy was used in the research. A variety of databases, including Pubmed, Proquest, and Willey Library Online, were used to choose the literature. Ten publications were selected as literature sources and were quantitatively analyzed descriptively. The lowest urea sigma matrix value was 1.3, and creatinine was -2.33, according to data from numerous publications, while the highest urea sigma matrix value was 5.81, and creatinine was 19.02. In the urea sigma matrix, the most widely distributed sigma matrix values was in the range <2 with the interpretation of the results was not acceptable. In the urea matrix, the highest distribution of sigma matrix values was in in the range 6 with world-class quality interpretation. It was concluded that in 15 research data from various journals there were 8 urea sigma matrix data that met the requirements, namely the sigma matrix value. 3 In 27 research data from various journals, there were 23 creatinine sigma matrix data that meet the requirements.